Photosynthesis Monitoring in Microalgae Mass Cultures - Malapascua, Jose Romel (Jihočeská univerzita, 2018)
This Ph.D. thesis deals with principles of microalgae cultivation in laboratory as well as outdoor aquacultures (Chapter 1) using various cultivation systems and photobioreactors (Chapter 2). Case studies illustrate the main research topic as to correlate changes in growth rate with variation of photosynthetic activity, physiological features and biomass composition (Chapter 3). Special attention was paid to elaboration of protocols of chlorophyll a fluorescence techniques for monitoring the physiology and photosynthetic performance of microalgae mass cultures maintained under various growth conditions (Chapter 4).
Photosynthesis Monitoring in Microalgae Mass Cultures
Keywords: microalgae; chlorophyll fluorescence; mass algal culture; photosynthesis; photobioreactors; microalgae; chlorophyll fluorescence; mass algal culture; photosynthesis; photobioreactors